Interferon-α2b Treatment for COVID-19 - Zhou, Qiong; Chen, Virginia; Shannon, Casey P.; Wei, Xiao-Shan; Xiang, Xuan; Wang, Xu; Wang, Zi-Hao; Tebbutt, Scott J.; Kollmann, Tobias R.; Fish, Eleanor N. (Frontiers in Immunology, 2020)
The global pandemic of COVID-19 cases caused by infection with SARS-CoV-2 is ongoing, with no approved antiviral intervention. We describe here the effects of treatment with interferon-α2b in a cohort of confirmed COVID-19 cases in Wuhan, China. In this uncontrolled, exploratory study, 77 adults hospitalized with confirmed COVID-19 were treated with either nebulized IFN-α2b (5mU b.i.d.), arbidol (200mg t.i.d.) or a combination of IFN-α2b plus arbidol. Serial SARS-CoV-2 testing along with hematological measurements, including cell counts, blood biochemistry and serum cytokine levels, and temperature and blood oxygen saturation levels, were recorded for each patient during their hospital stay. Treatment with IFN-α2b with or without arbidol significantly reduced the duration of detectable virus in the upper respiratory tract and in parallel reduced duration of elevated blood levels for the inflammatory markers IL-6 and CRP. These findings suggest that IFN-α2b should be further investigated as a therapy in COVID-19 cases.